Solid-Liquid Equilibrium Study of Binary System Saturated Fatty Acid in Short Chain Alcohols - Dwi Ardiana Setyawardhani; Difa Aulia Majid; Rudang Suryoadhi Suryatmoko Plawi (Program studi Teknik Kimia UNS, 2024)
Unsaturated fatty acids are potential to be used for preventing degenerative diseases and developing brain function in babies. Separation of unsaturated fatty acids from saturated fatty acids efficiently achieved by urea complexation fractionation method. It is considered to be the simplest, most efficient, and lowest cost method. This study aimed to optimize urea complexation for increasing PUFA concentrations by determining solid-liquid equilibrium data of saturated fatty acids in short chain alcohols. In this study, there were two types of short chain alcohol, methanol and ethanol, in various concentrations (99,7%; 95%; 88%; 76% w/w) towards the solubility of saturated fatty acids, palmitic and stearic acid (PA and SA). PA and SA dissolved in various concentrations of methanol and ethanol to get homogeneous solutions. When solid SFA disappeared by heating the solution, or first formed by cooling the solution, the temperature was determined as the solid-liquid equilibrium temperature. The results showed that the best composition of solvent within high solubility level is ethanol 95% and methanol 99,7% over palmitic acid because it can dissolve at room temperature and below 0.01 mole fraction.Keywords:Alcohol, Fatty Acid, Solid-Liquid Equilibrium, Solubility